A linguistic approach to the theme of language decadence. In consideration of whether language change should be a topic of interest for German as a foreign language - Foschi Albert, Marina (Glottodidactica, 2018)
The concept of language decadence can be interpreted in different ways: as mixing of languages, language deterioration, or language loss. As linguists are aware, all these manifestations commonly attributed to so-called language decadence are actually phenomena of language change. The debate on language decadence, while fascinating to public opinion, is based upon an abstract inconsistent view of language as a perfect, immutable instrument, to be used according to precise rules. Nevertheless, it is unavoidable in foreign language instruction to refer to rules and to a manageable model of standard language. The transmission of awareness about language change can avoid the creation of myths about language decadence